2013
DOI: 10.3389/fncom.2013.00091
|View full text |Cite
|
Sign up to set email alerts
|

A soft body as a reservoir: case studies in a dynamic model of octopus-inspired soft robotic arm

Abstract: The behaviors of the animals or embodied agents are characterized by the dynamic coupling between the brain, the body, and the environment. This implies that control, which is conventionally thought to be handled by the brain or a controller, can partially be outsourced to the physical body and the interaction with the environment. This idea has been demonstrated in a number of recently constructed robots, in particular from the field of “soft robotics”. Soft robots are made of a soft material introducing high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 55 publications
0
126
0
Order By: Relevance
“…Then, it is possible to autonomously generate a broad class of limit cycles, such as the Van der Pol oscillator, quadratic limit cycle, and Lissajous figures [28]. Importantly, these have been demonstrated in two different physical (simulated) reservoir computing setups: a mass-spring system [28] and an octopus arm [57].…”
Section: Computing With Masses and Springs Humanlike Bodies And Octmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, it is possible to autonomously generate a broad class of limit cycles, such as the Van der Pol oscillator, quadratic limit cycle, and Lissajous figures [28]. Importantly, these have been demonstrated in two different physical (simulated) reservoir computing setups: a mass-spring system [28] and an octopus arm [57].…”
Section: Computing With Masses and Springs Humanlike Bodies And Octmentioning
confidence: 99%
“…This very much blurs the boundaries between the brain as the seat of computing and the "mere physical body," in accordance with biological reality, which will be discussed in the next section. However, thus far the examples of this type [28,57,58,11,19,37] have a theoretical or proof-of-concept character, and their applicability remains to be proven ( Figure 9I-J).…”
Section: Morphological Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] It was then observed that the body dynamics may be used to control the arm's motion in a closed-loop manner by embedding nonlinear limit cycles. 8 However, the final step of bridging the gap between these findings and a robotic application was missing in previous works.…”
Section: Octopus Nervous Systemmentioning
confidence: 99%
“…Nakajima et al [26] extended the spring network to a biologically-inspired three-dimensional structure and it was shown that this body could also approximate filters and generate limit cycles. Finally, Zhao et al [36] replaced the spring network with the body of a spine-driven quadruped robot, referred to as 'Kitty', and used it to generate both locomotion and its own control signals.…”
Section: Introductionmentioning
confidence: 99%